London Sinfonietta: 'Spectrum of Sound' at Southbank Centre and White Cube Gallery residency, February/March 2015. (2nd July 2015) - Graham, Cameron
<x content-type="archive" xml:space="preserve">Abstract</x> How important is it for ensembles and orchestras to engage in performances outside of the typical concert environment? With a seemingly endless number of works commissioned and premiered every year, one could continue to experience new music without ever straying from the concert halls. Although cross-artistic endeavours between music and arts institutions are creating new and exciting performance environments, more often than not collaborative endeavours fail in their ability to communicate the relationship between mediums clearly and faithfully. Uniting different art forms into a single artistic experience is often seized as an opportunity to take music out of the concert hall and into more unorthodox performance spaces: do we need to see reputable music ensembles engage in projects with other art forms, or should organisations be created with this type of practice at the heart of their work?